Distribution of myogenic stem cell activator, hepatocyte growth factor, in skeletal muscle extracellular matrix and effect of short-term disuse and reloading - So Kuwakado; Alaa Elgaabari; Kahona Zushi; Sakiho Tanaka; Miyumi Seki; Ryuki Kaneko; Yuji Matsuyoshi; Takahiro Suzuki; Kenichi Kawaguchi; Yasuharu Nakashima; Ryuichi Tatsumi (PLoS ONE, 2025)
Hepatocyte growth factor (HGF) is a key myogenic stem cell (satellite cells) activator, that resides in the extracellular matrix (ECM). However, HGF distribution in the ECM varies depending on the muscle fiber type. Furthermore, aging impedes the binding of HGF to its receptors owing to nitration by peroxynitrite (ONOO - ). Though oxidative stress increases rapidly during muscle disuse atrophy, satellite cells are rapidly activated upon reloading. In this study, we investigated the distribution of HGF in the ECM in various muscle fiber types, and examined nitration of HGF in disuse and reloading models. Immunofluorescence staining was performed on the soleus (Sol), plantaris (Pla), and gastrocnemius (Gas) muscles of 10-week-old mice. Six mice were used to assess HGF distribution, while 12 mice, divided into control, disuse, and reloading groups were used for qualitative evaluation of nitrated HGF (nitroHGF). Student’s t-tests and the Bonferroni correction were employed for statistical analysis ( p < 0.05/3 = 0.0167). In Sol muscle, type IIa and IIx muscle fibers exhibited higher HGF distribution in the ECM (61.5 ± 1.0% and 56.7 ± 1.1%, respectively) than type I fibers (32.3 ± 1.0%; p < 0.001). In Pla and Gas muscle, type IIa 55.8 ± 0.9% and 58.8 ± 1.5%, respectively) and type IIx fibers (49.6 ± 0.9% and 48.9 ± 1.1%, respectively) had significantly higher HGF distribution in the ECM than type IIb fibers (18.6 ± 0.9% and 13.0 ± 1.0%; p < 0.001, respectively). The amount of nitroHGF increased in the disuse group compared to that in the control group but decreased in the reloading group compared to that in the disuse group. This preferential HGF distribution around type IIa and IIx muscle fibers indicates a distinct mechanism for satellite cell activation, differing from the satellite cell-rich environment associated with type I fibers and the lower HGF association with type IIb fibers. Disuse-induced HGF nitration may inhibit satellite cell activation. Reloading likely triggers mechanisms that counteract nitration, enabling satellite cell reactivation in young muscle.